Impact of Fumigants on Soil Microbial Communities - Ibekwe, A. Mark (American Society for Microbiology, 2001)
Agricultural soils are typically fumigated to provide effective control of nematodes, soilborne pathogens, and weeds in preparation for planting of high-value cash crops. The ability of soil microbial communities to recover after treatment with fumigants was examined using culture-dependent (Biolog) and culture-independent (phospholipid fatty acid [PLFA] analysis and denaturing gradient gel electrophoresis [DGGE] of 16S ribosomal DNA [rDNA] fragments amplified directly from soil DNA) approaches. Changes in soil microbial community structure were examined in a microcosm experiment following the application of methyl bromide (MeBr), methyl isothiocyanate, 1,3-dichloropropene (1,3-D), and chloropicrin. Variations among Biolog fingerprints showed that the effect of MeBr on heterotrophic microbial activities was most severe in the first week and that thereafter the effects of MeBr and the other fumigants were expressed at much lower levels. The results of PLFA analysis demonstrated a community shift in all treatments to a community dominated by gram-positive bacterial biomass. Different 16S rDNA profiles from fumigated soils were quantified by analyzing the DGGE band patterns. The Shannon-Weaver index of diversity, H, was calculated for each fumigated soil sample. High diversity indices were maintained between the control soil and the fumigant-treated soils, except for MeBr (H decreased from 1.14 to 0.13). After 12 weeks of incubation, H increased to 0.73 in the MeBr-treated samples. Sequence analysis of clones generated from unique bands showed the presence of taxonomically unique clones that had emerged from the MeBr-treated samples and were dominated by clones closely related to Bacillus spp. and Heliothrix oregonensis. Variations in the data were much higher in the Biolog assay than in the PLFA and DGGE assays, suggesting a high sensitivity of PLFA analysis and DGGE in monitoring the effects of fumigants on soil community composition and structure. Our results indicate that MeBr has the greatest impact on soil microbial communities and that 1,3-D has the least impact.